Spontaneous omental infarction in an obese young female patient treated with laparoscopy: a case report - Nikolovski, Andrej; Lazarova, Ana; Mojsilovic, Dino; Ristovski, Gligor; Argirov, Ivan; Ulusoy, Cemal (Oxford University Press (OUP), 2024)
Partial infarction of the great omentum is a rare cause of abdominal pain and may present as a surgical emergency. Omental infarction might occur due to its torsion, but cases without obvious cause are reported. Risk factors related to this condition are overweight, obesity, abdominal trauma, recent abdominal surgery, hypercoagulability, postprandial vascular congestion and an increase in intra-abdominal pressure. Because of the condition's rarity, most patients are treated with surgery and the diagnosis is established intraoperatively. Preoperative diagnosis allows successful conservative treatment with analgesics and anti-inflammatory drugs. This case reports a young female patient with class III obesity presented with spontaneous partial infarction of the great omentum treated with laparoscopy.
Keywords: omental infarction; obesity; treatment; laparoscopy